2019
DOI: 10.1016/j.bbmt.2018.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Parainfluenza Virus Lower Respiratory Tract Disease after Hematopoietic Cell Transplantation

Abstract: Parainfluenza virus (PIV) infection can progress from upper respiratory tract infection (URTI) to lower respiratory tract disease (LRTD) in immunocompromised hosts. Risk factors for progression to LRTD and presentation with LRTD without prior URTI are poorly defined. Hematopoietic cell transplant (HCT) recipients with PIV infection were retrospectively analyzed using standardized definitions of LRTD. PIV was detected in 540 HCT recipients; 343 had URTI alone and 197 (36%) had LRTD (possible, 76; probable, 19; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
(60 reference statements)
2
29
1
Order By: Relevance
“…No patients who lacked all of these risk factors progressed to LRTI, whereas the progression risk increased to greater than 30% if 3 or more risk factors were present. 64 The need for mechanical ventilation in those with LRTI was 43% and survival from onset of mechanical ventilation was 23%. Although overall mortality with PIV LRTI is high after transplant, mortality decreases with time from transplant.…”
Section: Virus Specifics: Outcomes and Treatment Influenza A/bmentioning
confidence: 97%
See 2 more Smart Citations
“…No patients who lacked all of these risk factors progressed to LRTI, whereas the progression risk increased to greater than 30% if 3 or more risk factors were present. 64 The need for mechanical ventilation in those with LRTI was 43% and survival from onset of mechanical ventilation was 23%. Although overall mortality with PIV LRTI is high after transplant, mortality decreases with time from transplant.…”
Section: Virus Specifics: Outcomes and Treatment Influenza A/bmentioning
confidence: 97%
“…The use of adjuvant steroids is not advised, because high-dose steroids generally are associated with increased risk of progression to LRTI, prolonged viral shedding, and increased mortality. 9,21,45,53,[62][63][64] As such, consideration should be given to decreasing the steroid dose whenever feasible to less than 1 mg per/kg/d.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no approved drugs that have been demonstrated to be active against HPIV clinically. While most studies have failed to demonstrate a clinical benefit, especially for advanced stages (31,162), many clinicians will administer IVIG and, less frequently, oral or aerosolized ribavirin for high-risk patients (5,73) (Table 4) despite lack of evidence for efficacy, especially for lower RTID.…”
Section: Human Pneumo-and Paramyxoviridaementioning
confidence: 99%
“…Parainfluenza virus (PIV) infection is one of the most common respiratory virus infections and is a significant cause of morbidity and mortality, especially in patients with hematologic malignancy including recipients of hematopoietic stem cell transplantation (HCT) [1][2][3][4][5][6]. Previous studies have identified various risk factors for the progression of PIV infection to pneumonia and attrib-utable mortality in recipients of HCT [7][8][9][10]. In addition, the efficacy of ribavirin (aerosolized, intravenous, or oral) in previous studies showed mixed results [9,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%